JHMN 2019
DOI: 10.7176/jhmn/63-04
|View full text |Cite
|
Sign up to set email alerts
|

Partograph Utilization and Factors Associated with Poor Perinatal Outcomes in Wolaita Sodo University Referral Hospital, Southern Ethiopia

Abstract: Background: Maternal deaths remain a major public health problem worldwide. The World Health Organization (WHO) has recommended the use of modified WHO partograph to monitor labour and delivery, in order to improve delivery care and reduce maternal and perinatal mortality rate. Objective: This study was aimed to assess utilization of partograph and factors associated with perinatal outcomes among women who delivered at wolaita sodo university teaching referral hospital.Methods: A facility based cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 8 publications
2
2
0
Order By: Relevance
“…Similarly, Jere ( 2014 :39) reported adverse neonatal outcomes of low Apgar scores and fresh stillbirths. These results are consistent with the research conducted by Rani et al ( 2016 :316) and Chemeda et al ( 2019 :36), which discovered that a noteworthy proportion of newborns were small for gestational age, had septicaemia, neonatal jaundice, low Apgar score and birth asphyxia. Appropriate application of the partogram allows for the diagnosis of prolonged and obstructed labour and decreases infant problems such as anoxia, infections, mortality and stillbirth risks (Dippenaar & Da Serra 2018 :399).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Similarly, Jere ( 2014 :39) reported adverse neonatal outcomes of low Apgar scores and fresh stillbirths. These results are consistent with the research conducted by Rani et al ( 2016 :316) and Chemeda et al ( 2019 :36), which discovered that a noteworthy proportion of newborns were small for gestational age, had septicaemia, neonatal jaundice, low Apgar score and birth asphyxia. Appropriate application of the partogram allows for the diagnosis of prolonged and obstructed labour and decreases infant problems such as anoxia, infections, mortality and stillbirth risks (Dippenaar & Da Serra 2018 :399).…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, Maphasha et al ( 2017 :84) confirmed that healthcare workers could not plot moulding, caput and FHR. This is consistent with the study conducted by Chemeda, Teklewold and Daka ( 2019 :36) with low standard recordings in mouldings (2%), liquor status (3.2%) and descent (3.9%). The foetal brain is protected from compression if the moulding is not increasing or excessive.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations